Facing Ageism: Toward a Christian Response - Makins, Leslie A. (My University, 2014)
Most people in Western culture are inclined, if not obsessed, with the need to maintain perpetual youthfulness in their actions, attitudes, and image. This cultural ideal is fueled by inner fear as well as age-related stereotypes, prejudice, media messaging, consumerism, and lifestyle strategies. Most of these age-related factors are connected to "ageism," a 1969 term coined by Robert Butler. While the majority of people display various ageist attitudes, often it is without awareness. In a culture that is so profoundly accepting of such a phenomenon, individuals and the church should consider an appropriate Christian response in light of ageism's impacts that include discrimination, loss of self-worth, fear of aging, and judgment of self and others. Once aware of its prevalence and impact, this thesis proposes that the church can respond by raising awareness of ageism and its implications, and modeling a "better way" in its daily life and ministry.
Keywords: ageism, Christian, response, culture, Western culture